Updated approaches for management of uterine fibroids - Mas A; Tarazona M; Dasí Carrasco J; Estaca G; Cristóbal I; Monleón J (Dove Medical Press, 2017)
Aymara Mas,1,2 Marta Tarazona,3 Joana Dasí Carrasco,3 Gloria Estaca,4,5 Ignacio Cristóbal,4,5 Javier Monleón3 1Reproductive Medicine Research Group, Institute of Health Research La Fe, University and Polytechnic Hospital La Fe, Valencia, Spain; 2Research and Development Department, Igenomix Foundation, Valencia, Spain; 3Gynecology Department, University and Polytechnic Hospital La Fe, Valencia, Spain; 4Obstetrics and Gynecology Department, La Zarzuela Hospital, Madrid, Spain; 5Obstetrics and Gynecology Department, Universidad Francisco de Vitoria, Madrid, Spain Abstract: Uterine anatomy and uterine fibroids (UFs) characteristics have been classically considered as almost a unique issue in gynecology and reproductive medicine. Nowadays, the management of UF pathology is undergoing an important evolution, with the patient’s quality of life being the most important aspect to consider. Accordingly, surgical techniques and aggressive treatments are reserved for only those cases with heavy symptomatology, while the clinical diagnostic based on size and number of UFs remains in a second plane in these situations. Moreover, the development of several noninvasive surgical techniques, especially the appearance of ulipristal acetate as a medical etiological treatment, has substantially changed the clinical indications. As a consequence, after almost 2 decades without relevant updates, it has been necessary to update the protocols for the management of UFs in the Spanish Society of Gynecology and Obstetrics twice. Accordingly, we believe that it is necessary to translate our experience to protocolize the medical care for patients with UFs, incorporating these new therapeutic options, and selecting the best treatment for them. We highlight the importance of achieving the patient’s goals and decisions by improving the clinical diagnosis for these type of pathologies, allowing enhanced personalized treatments, as well as the reduction of potential risks and unnecessary surgeries. Keywords: uterine fibroids, UFs, selective progesterone receptor modulator, sPRM, ulipristal acetate, UPA